Autologous and implant based immediate breast reconstructive trends following unilateral modified radical and radical mastectomy: a SEER database analysis - Jian H. Li; Stephen A. Stearns; Angelica Hernandez Alvarez; Samuel J. Lin (Journal of Plastic Surgery and Hand Surgery)
Longitudinal trends in breast reconstruction after modified radical mastectomy remain under described. This study aims to assess procedural trends in autologous reconstruction (AR) and implant-based reconstruction (IBR), to analyse demographic shifts in these patients, and to examine differences in oncologic management. This retrospective study utilizes the Surveillance, Epidemiology, and End Results (SEER) database to investigate trends in immediate breast reconstruction from 2000 to 2020 following unilateral modified radical and radical mastectomy. Demographic and oncologic variables were collected, and reconstruction types were categorised as IBR, AR, or a combination. Subgroup analyses compared IBR and AR patients, and demographic changes between the 2000–2010 and 2010–2020 cohorts were examined. Chi-square tests in R studio were used for statistical analysis. Of the 25,649 patients, 51.8% underwent IBR and 48.2% AR. AR patients were typically younger, more frequently Black, had higher incomes, and were less likely to live in rural areas compared to IBR patients. A shift from AR to IBR was observed, with AR decreasing from 41.8% in 2000 to 24.5% in 2020. Significant demographic changes in AR patients included increased age, higher proportions of Black and Asian patients, reduced income, and increased non-marital status. Oncologic management differed, as AR patients were less likely to have received chemotherapy and radiation prior to their reconstruction, and experienced longer reconstruction times compared to IBR patients. This study highlights a decline in AR and rising IBR popularity, and reveals evolving patient characteristics. Understanding these trends is crucial for equitable access and informed decision-making in breast cancer reconstructive care.